2006
DOI: 10.1177/000331970605700306
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum Insulin-like Growth Factor-1 and C-Reactive Protein in Metabolic Syndrome With or Without Diabetes

Abstract: There are only a few data on the relationship of insulin-like growth factor-1 (IGF-1), implicated in glucose homeostasis, and C-reactive protein (CRP), a measure of subclinical systemic inflammation, in patients with the metabolic syndrome (MetS). The authors investigated, in a cross-sectional design, the correlation between total IGF-1 and CRP in 170 subjects. Among them 123 had the MetS (National Cholesterol Program ATP III definition) and 47 did not, and 136 had type 2 diabetes mellitus (DM) and 34 did not.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…In cohorts with older subjects, the findings are more heterogeneous. A small study in older people showed an association of low IGF1 concentrations with the metabolic syndrome (24), although an Italian cohort demonstrated no significant associations in older women, and a trend toward higher IGF1 values in men with the metabolic syndrome (25,26). Most recently, Yeap et al (10) studied a cohort of men of 70 years and older and found a U-shaped relationship, with increased risks for metabolic syndrome at the lower and upper end of IGF1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In cohorts with older subjects, the findings are more heterogeneous. A small study in older people showed an association of low IGF1 concentrations with the metabolic syndrome (24), although an Italian cohort demonstrated no significant associations in older women, and a trend toward higher IGF1 values in men with the metabolic syndrome (25,26). Most recently, Yeap et al (10) studied a cohort of men of 70 years and older and found a U-shaped relationship, with increased risks for metabolic syndrome at the lower and upper end of IGF1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, it has been shown that low IGF-I leads to high insulin levels and increased serum lipid levels [18]. In human studies, however, the relationship of metabolic syndrome, or some of the components of metabolic syndrome, with IGF-I, IGF-BP3 or the ratio of IGF-I/IGF-BP3 has been examined only in small, patient-based or select populations [19][20][21][22][23][24] that are not population based or nationally representative. A recent nationally representative study of young adults found a low IGF-I/IGF-BP3 ratio to be significantly associated with the metabolic syndrome [25].…”
Section: Introductionmentioning
confidence: 99%
“…A recent nationally representative study of young adults found a low IGF-I/IGF-BP3 ratio to be significantly associated with the metabolic syndrome [25]. Although the results are inconsistent, many studies found decreased levels of IGF-I associated with components of metabolic syndrome [19,20,22,23]. Some examples include C-reactive protein, a marker of subclinical inflammation in metabolic syndrome and a risk factor for heart disease that is negatively correlated with IGF-I concentrations [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual role could explain the admixture of insulin resistance and sensitivity that is commonly observed in the metabolic syndrome (37). IGF1 Individuals with metabolic syndrome had lower IGF-1 levels than subjects without metabolic syndrome with an almost linear decline of IGF-1 levels as the number of fulfilled criteria of the metabolic syndrome (none to 5) increased (16). INSR A muscle-specific insulin receptor knockout exhibits features of the metabolic syndrome of NIDDM (10,25).…”
Section: Apobmentioning
confidence: 99%